Autonomous and Manual Control robot - Ghodichor, Nitesh; Bhawna, Surabhi; *, Akshay; *, Satyam; *, Rakesh; *, Govind; *, Mahvash (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
This paper explores the implementation of Bluetoothtechnology in mobile robots, to give robots the capability to move around using Bluetooth signal given transmitted by Bluetooth enableAndroid smartphone.Some powerful algorithm is stored inside the microcontroller. And robot also moves autonomously using IR sensors.